Sudden death in childhood and adolescence. Issue 9 (September 2019) - Al-Adnani, Mudher; George, Simi; Marnerides, Andreas
Abstract: Sudden death in childhood and adolescence is fortunately rare. However, when it occurs, it can have a devastating effect on the family. Therefore, these cases should be thoroughly investigated, including a complete post mortem examination by a specialist in paediatric pathology. The aim is to identify the cause of death, and potentially prevent future deaths. This review will provide an overview of the epidemiology of sudden death in childhood and adolescence and will outline the wide range of causes of death identified. Certain aspects of the paediatric post mortem examination will be discussed, and will finish with a section on deaths in children with chronic medical conditions.